Africa Development Indicators 2010: Silent and Lethal -- How Quiet Corruption Undermines Africa's Development Efforts (World Bank Publications, Washington, DC, 2010)
NNThe World Bank came into formal existence in 1945 following the international ratification of the Bretton Woods agreements. It is a vital source of financial and technical assistance to developing countries around the world. The organization's activities are focused on education, health, agriculture and rural development, environmental protection, establishing and enforcing regulations, infrastructure development, governance and legal institutions development. The World Bank is made up of two unique development institutions owned by its 185 Member Countries. The International Bank for Reconstruction and Development (IBRD) focuses on middle income and creditworthy poor countries and the International Development Association (IDA), which focuses on the poorest countries in the world.
Keywords: Business Encyclopedias; Business Education & Reference